Automated Security Configuration Management for Enterprise Networking Products - Jaskirat Singh Chauhan, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive analysis of automated security configuration management for enterprise networking products, addressing the growing challenges in maintaining secure network configurations across complex modern infrastructures. It examines the evolution of network configuration management from traditional manual approaches to automated solutions, highlighting the critical role of automation in maintaining security posture and compliance. Through analysis of recent research and industry reports, the article explores the challenges posed by increasing network complexity, particularly in hybrid environments combining on-premises and cloud-based services. It investigates the components of automated configuration analysis systems, including scanning engines, security rule engines, and remediation recommendation systems. The article demonstrates the benefits of automated configuration management, including improved security consistency, reduced human error, enhanced proactive risk management, and streamlined compliance processes. It also provides detailed implementation considerations for organizations adopting automated configuration management solutions, emphasizing the importance of establishing clear security baselines, robust change management procedures, and regular updates to security rules and best practices.
Keywords: Compliance Management; Configuration Analysis; Security Automation; Enterprise Network Security; Network Configuration Management